ANALISIS FAKTOR YANG MEMPENGARUHI SEKS PRANIKAH PADA REMAJA PUTRI DI DESA PARDOMUAN TOBA SAMOSIR - Pangaribuan, Ingka Kristina; Simbolon, Marlina; Napitupulu, Yuki (LPPM Universitas Sari Mulia, 2022)
Background: Adolescence is a transition period from children to adults. Youth life is a life that is very decisive for their future life. Based on data from the Indonesian Young Adult Reproductive Health Survey (IYARHS) in 2012, girls and boys aged 15-24 years stated that they had had premarital sexual intercourse with 1% for women and 6% for men respectively. Objective: To analyze the factors that influence premarital sex among young woman in the village of Pardomuan Toba Samosir Method: This research is a survey research type with a cross sectional approach with a sample of 75 young women using a total sampling technique. The research instrument used) and data analysis using chi square. There is a significant relationship between knowledge of premarital sex among young women in the village of Pardomuan Toba Samosir 2020 with a value of p <0.05; RP 2.883, there is a significant relationship between attitudes towards premarital sex among young women in the Village of Pardomuan Toba Samosir 2020 with a value of p <0.05; RP 2.883, there is no significant relationship between parental supervision of premarital sex among young women in the village of Pardomuan Toba Samosir 2020 with a value of p> 0.05; RP 3,763, there is a significant relationship between media information on premarital sex among young women in Pardomuan Village Toba Samosir 2020 with a value of p> 0,000; IDR 6,222 Conclusion: The most significant factor causing premarital sex in adolescents is information media with a value of p = 0.000 and what is not related to this study is parental supervision with a value of p <0.008